On Implicit Elicitation of Cognitive Strategies using Gaze Transition Entropies in Pattern Recognition Tasks - Raptis, George E.; Fidas, Christos A.; Avouris, Nikolaos M. (Proceedings of the 2017 CHI Conference Extended Abstracts on Human Factors in Computing Systems - CHI EA '17, 2017)
Recent research provides evidence that individual differences on human cognitive strategies affect user performance and experience in diverse application domains. However, state-of-the-art elicitation methods of human cognitive strategies require from researchers to apply explicit, in-lab, and time-consuming "paper-and-pencil" techniques, compromising real-time integration of human cognitive strategies in interactive system design. Aiming to elaborate an implicit elicitation framework of human cognitive strategies, this paper reports on an in-lab eye-tracking study, which embraced sixty seven participants, who performed a credible "paper-and-pencil" cognitive strategy elicitation technique. Eye tracking analysis based on gaze transition entropies revealed quantitative differences on visual search patterns among individuals within visual pattern recognition tasks of varying complexity. Results of this study could drive the development of an implicit elicitation framework of human cognitive strategies.